PENGEMBANGAN POP UP BOOK BERBASIS DEEP LEARNING MATERI KENAMPAKAN ALAM UNTUK MENINGKATKAN SELF REGULATED LEARNING SISWA - Fatqul Anang Ma'ruf; Mohamad Fatih; Ragil Tri Oktaviani (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aimed to develop a Deep Learning-based Pop Up Book on Natural Landscape material to improve Self Regulated Learning (SRL) among Grade IV students at UPT SD Negeri Sentul 01, Blitar City. The study employed the Research and Development (R&D) method adapting the Borg and Gall model into 7 stages, combined with a Quasi Experimental Design using Pretest-Posttest Control Group Design. Eighteen Grade IV students were divided into a control class (9 students) and an experimental class (9 students). Data were collected through observation, interviews, validation questionnaires, and SRL questionnaires. Content expert validation yielded 100% (very valid), media expert validation yielded 91% (very valid), and teacher practicality assessment yielded 100% (very feasible). The Paired Sample T-Test for the control class obtained a significance value of 0.000 < 0.05, with mean scores increasing from 72.89 to 77.00. The experimental class showed a higher mean increase, from 71.22 to 85.00. The Independent Sample T-Test showed a significance value of 0.000 < 0.05 with a mean post-questionnaire difference of 8 points, where the experimental class (85.00) outperformed the control class (77.00). Therefore, the Deep Learning-based Pop Up Book is proven valid, feasible, and effective in improving Self Regulated Learning among Grade IV elementary school students.